(untitled) (Rivista di Studi e Ricerche sulla criminalità organizzata, 2025)
The article summarizes the key points of Piersanti Mattarella’s address to the Sicilian Regional Assembly on November 20th, 1979, featured below. In his speech, Mattarella forcefully condemns Mafia violence and calls on the State to respond decisively. The introduction emphasizes his belief that the fight against the Mafia must go beyond repression and instead involve institutional reform, economic development, and government transparency — in other words, the pursuit of “good politics.”